Urban food sharing: Emerging geographies of production, consumption and exchange. Issue 99 (February 2019) - Davies, Anna; Evans, David
Abstract: The role of urban areas in shaping global futures has never been clearer. However, their complex socio-technical systems are under stress and unlikely to experience any respite as populations grow and as patterns of production and consumption resist transition to more sustainable pathways. Urban food systems are not exempt from these pressures, however they are the subject of ongoing experimentation and innovation, particularly around the use of information and communication technologies (ICT). Urban food sharing is one such arena of experimentation. It includes collective and collaborative practices around food, from shared growing, cooking and eating and the redistribution of surplus food, to the sharing of spaces and devices. This themed issue brings together cutting-edge scholarship on what it means to share food in contemporary cities around the globe. All papers contribute to debates about how things become food, whether that is in relation to the rules and governing systems that shape and discipline these becomings, or the practices of exchange and consumption that follow. Together they develop geographically-sensitive approaches to sharing that better comprehend the relations between scale, space and place. This paper maps the terrain of urban food sharing, introduces key conceptual approaches, identifies common themes, and proposes an agenda for future studies.